Integrated Pest Management of Wireworms in Potatoes: Use of Tolerant Varieties to Implement Damage Prevention - Furlan Lorenzo; Bona Stefano; Benvegnù Isadora; Cacitti Valentina; Govoni Fausto; Parisi Bruno (Insects)
Wireworms (Agriotes spp., Coleoptera, Elateridae) are a major threat to potatoes, as are the current commercial standards for assessing potato damage. To reduce wireworm impacts on potato crops and comply with IPM legislation, we started research to assess the potential for new Italian 4x-breeding clones to reduce wireworm feeding on daughter tubers. Two sets of trials were carried out over a six-year period (2018–2023): in-field and in semi-natural conditions, with pots used to introduce a set number of reared wireworms. In the field trials, the varieties were planted in 4.8 × 9–12 m plots in a randomized-block layout with at least three replications. The same wireworm damage assessment was used for both sets of trials. The assessment involved counting all the erosions/scars caused by wireworm feeding activity. The prevalent wireworm species studied was Agriotes sordidus. Both sets of trials showed that some 4x-breeding clones were tolerant to wireworm attacks. The percentages of tubers damaged (any symptom) or with at least one ordinary/large hole was up to five times lower than in the commercial varieties. Glycoalkaloids and the caffeic acid content in tubers are considered to be the main cause of lower appetibility to wireworms.